2009
DOI: 10.4065/84.6.509
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Video-Assisted Thoracoscopic Lobectomy

Abstract: This article is freely available on publication, because the authors have chosen the immediate access option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 40 publications
1
13
1
5
Order By: Relevance
“…Criteria for operability have evolved in recent years, as it has become evident that surgery in carefully selected patients of advanced age and with impaired lung function may be a safe and feasible treatment option and can be associated with reasonable quality of life outcomes in spite of a higher incidence of postoperative complications. [7][8][9][10][11][12][13][14] To determine whether the patient may tolerate general anesthesia and pulmonary resection, a thorough medical history should be obtained. Patients who have experienced angina pectoris or similar symptoms in the past or those with known underlying cardiovascular disease should be risk stratified by additional functional testing.…”
Section: Considerations Prior To Surgical Resectionmentioning
confidence: 99%
“…Criteria for operability have evolved in recent years, as it has become evident that surgery in carefully selected patients of advanced age and with impaired lung function may be a safe and feasible treatment option and can be associated with reasonable quality of life outcomes in spite of a higher incidence of postoperative complications. [7][8][9][10][11][12][13][14] To determine whether the patient may tolerate general anesthesia and pulmonary resection, a thorough medical history should be obtained. Patients who have experienced angina pectoris or similar symptoms in the past or those with known underlying cardiovascular disease should be risk stratified by additional functional testing.…”
Section: Considerations Prior To Surgical Resectionmentioning
confidence: 99%
“…VATS lobectomy offers more advantages than thoracotomy lobectomy in terms of short‐term postoperative outcomes, including less postoperative pain, faster postoperative recovery, greater preservation of pulmonary function, and lower perioperative morbidity . Moreover, VATS lobectomy is equivalent to thoracotomy in terms of oncologic outcomes, including survival and recurrence rates …”
Section: Introductionmentioning
confidence: 99%
“…3 Moreover, VATS lobectomy is equivalent to thoracotomy in terms of oncologic outcomes, including survival and recurrence rates. 4,5 Recent studies have suggested that surgical resection following neoadjuvant chemotherapy for patients with locally advanced NSCLC can significantly improve the complete surgical resection (R0) rate and long-term survival. 2,6,7 However, the feasibility and clinical efficacy of performing VATS pulmonary resection after neoadjuvant CRT remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…VATS lobectomy is thought to have more advantages than lobectomy under thoracotomy in postoperative pain [4], postoperative recovery [5], preservation of pulmonary function [6], immune surveillance [7], and surgical complications [8]. In addition, oncologic studies have showed VATS lobectomy is equivalent to thoracotomy in overall survival and recurrence rate [9,10].…”
mentioning
confidence: 99%